2022
DOI: 10.1200/jco.2022.40.16_suppl.e20551
|View full text |Cite
|
Sign up to set email alerts
|

Detection of early-stage lung cancer with an in vitro panel of activity-based biosensors to measure inflammatory protease enzymes.

Abstract: e20551 Background: Enzyme activity is at the center of all biological processes. When these activities are misregulated by changes in sequence, expression, or activity, pathologies emerge. Misregulation of protease enzymes such as Matrix Metalloproteinases and Cathepsins play a key role in the pathophysiology of cancer. We describe here a novel class of graphene-based, cost effective biosensors that can detect altered protease activation in a blood sample from early stage lung cancer patients. Methods: The Ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…4 ). This list was expanded to include peptides designed in previous studies which had shown different protease enzyme profiles in breast, pancreatic and lung cancers (Table 1 ) 18 , 25 27 . We also manufactured a sensor for Arginase activity which responds to the post-translational deamination of arginine to ornithine 28 and contributes to regulation of anti-tumor inflammatory responses 29 , 30 .…”
Section: Resultsmentioning
confidence: 99%
“…4 ). This list was expanded to include peptides designed in previous studies which had shown different protease enzyme profiles in breast, pancreatic and lung cancers (Table 1 ) 18 , 25 27 . We also manufactured a sensor for Arginase activity which responds to the post-translational deamination of arginine to ornithine 28 and contributes to regulation of anti-tumor inflammatory responses 29 , 30 .…”
Section: Resultsmentioning
confidence: 99%